2019
DOI: 10.1155/2019/4625912
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Exerts a Myocardial Protective Effect against Cardiac Hypertrophy in Rats, Partially via Activating the Nrf2/HO-1 Signaling Pathway

Abstract: Previous evidence suggested that astragaloside IV (ASIV) had a cardioprotective effect, but the potential mechanisms were undetermined. This study is aimed at validating the prevention of cardiac hypertrophy in chronic heart failure (CHF) rats and hypertrophy in H9c2 cardiomyocytes by ASIV and at exploring the potential mechanism involved. CHF rat models of abdominal aortic constriction (AAC) were used with the aim of determining the protective effect of ASIV in cardiac hypertrophy in the rats. We proved that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 58 publications
5
39
0
1
Order By: Relevance
“…Such a result was consistent with recently published data showing that ASI induced Nrf2/HO-1 protein expressions in the myocardium in a rat model of abdominal aortic constriction (Nie et al. 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such a result was consistent with recently published data showing that ASI induced Nrf2/HO-1 protein expressions in the myocardium in a rat model of abdominal aortic constriction (Nie et al. 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we reported increased protein expression of Nrf2 and its downstream signal molecule HO-1 in the myocardial tissue of HF rats. Such a result was consistent with recently published data showing that ASI induced Nrf2/HO-1 protein expressions in the myocardium in a rat model of abdominal aortic constriction (Nie et al 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, research confirms that cycloastragenol improves cardiac defect and remodeling by enhancing autophagy in myocardial cells and reduces the production of MMP-2 and MMP-9 [24]. Previous studies suggest that astragaloside IV corrects cardiac dysfunction and reduces myocardial hypertrophy by activating Nrf2/ HO-1 pathway and PI3K/mTOR pathway and can promote angiogenesis [37][38][39]. is study recruited both identified compounds from TCMSP and the compounds with outstanding pharmacological effects.…”
Section: Discussionmentioning
confidence: 67%
“…Among the chemical components, 68% of them were higher in MJ than in MG. Besides, four primary saponins constituents including Astragaloside I, Astragaloside II, Astragaloside III, and especially Astragaloside IV with anti-cancer [28], anti-oxidant [29], anti-inflammatory [30], immune regulation [31], and metabolic regulation activities [32], among others [33,34,35], in MJ were distinctly higher than that in MG. The result offered evidence that MJ may own stronger pharmacological activity and wider application than MG.…”
Section: Resultsmentioning
confidence: 99%